Pelatihan dan Pendampingan Kelompok Tani Anggrek dalam Pembuatan Pestisida Biorasional Lantana sebagai pengendali OPT Tanaman Anggrek untuk Mencapai Asta Cita - Utama, Hanif Hadinata; Sugianto, Ferdy; Sukamto, Dwi Sucianingtyas; Danuji, Sarwo (Dedication : Jurnal Pengabdian Masyarakat, 2026)
This community service activity was conducted on October 5, 2025, at the orchid garden of the Puspa Pesona Farmer Group located in Silo District, Jember Regency. The partner group consists of 10 members who cultivate various orchid species, including Dendrobium, Vanda, and Cattleya, on a 2,000 m² area. The main problem faced by the farmers is the decline in production quality due to attacks from Plant Pest Organisms (PPO), such as mites (T. orchidarum and P. vandergooti), thrips (D. smithi), and the bacterium Erwinia carotovora, which causes stem and leaf rot. This activity aimed to improve production quality and farmers’ management capacity through training on the production of biopesticides made from Lantana camara leaves. This plant contains active compounds such as alkaloids, flavonoids, and tannins that function as natural insecticides and antibacterial agents. The training included theoretical sessions, demonstrations, fermentation, filtration, packaging, and application to infected orchids. The results indicated increased farmer knowledge and practical skills in environmentally friendly pest management, reduced pest attacks, and greater awareness of sustainable orchid cultivation practices.